2018
DOI: 10.1177/1758573218756866
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and classification of osteochondritis dissecans of the capitellum: X-ray, magnetic resonance imaging or computed tomography?

Abstract: Background: Diagnosing capitellar osteochondritis dissecans (OCD) can be difficult, causing delay in treating young athletes. The main aim of this retrospective diagnostic study was to determine which radiological technique is preferred to identify and classify elbow OCD. Methods: We identified young patients who underwent elbow arthroscopy because of symptomatic OCD. We included all patients who had pre-operative radiographs, a computed tomography (CT) scan and magnetic resonance imaging (MRI) available. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Previous investigations have demonstrated variable ability of AP and lateral radiographs to detect capitellum OCD, with success of approximately 47% to 76%. 7,17 In a recent review of 25 patients (mean age, 17 years) with known symptomatic capitellum OCD lesions, van den Ende et al 17 found that 24% of lesions were not identified on standard AP and lateral radiographs. Moreover, the lesion was noted in only 36% of patients using AP views alone, while in only 40% of patients, the lesion was identified on both AP and lateral views.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have demonstrated variable ability of AP and lateral radiographs to detect capitellum OCD, with success of approximately 47% to 76%. 7,17 In a recent review of 25 patients (mean age, 17 years) with known symptomatic capitellum OCD lesions, van den Ende et al 17 found that 24% of lesions were not identified on standard AP and lateral radiographs. Moreover, the lesion was noted in only 36% of patients using AP views alone, while in only 40% of patients, the lesion was identified on both AP and lateral views.…”
Section: Discussionmentioning
confidence: 99%
“…9,16 Treatment of symptomatic capitellum OCD is primarily based on lesion stability, size, and location, which are best assessed with advanced imaging (eg, computed tomography [CT] and magnetic resonance imaging [MRI]). [11][12][13]17 Stable lesions can be successfully treated with nonsurgical treatment, including activity modification. 10 Unstable lesions, particularly when there is disruption of a segment of cartilage from subchondral bone, require operative intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographs, however, have been shown to have poorer sensitivity than MRI or even computed tomography imaging when detecting osteochondral lesions. 13,28 Although computed tomography has been used to evaluate healing, it does not appear to correlate with outcome measures. 2 As such, the radiographic healing evident in all the patients in the present study may not be of high utility in counseling patients and parents on functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,12,21,29 Computed tomography (CT) has not had an apparent, important role in the literature for diagnosing OCD. 21,26 Although CT has not been compared with MRI for staging OCD, 7,15,27 CT is useful for detection of OCD fragmentation, loose bodies, and sclerosis. 21,25,26…”
mentioning
confidence: 99%